SIFAT PERTUMBUHAN DAN INDEKS KONDISI Geloina coaxans DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN KOTA TARAKAN - Gazali, Salim (Jurnal Harpodon Borneo, 2018)
Research objectives is to know the nature of allometri growth and an index the condition of Geloina coaxans that is in KKMB Tarakan city.Methods used is descriptive quantitative. The research uses a method of the determination of purposive the sampling method. The sample collection as many as 12 a plot in the area of the expansion of KKMB Tarakan city. A plot measuring 10 x 10 m and the distance each a plot as far as 10 m.The results of research the regression equation is between long the shell of a to the weight of the y = 2.4418x-4.0447 is growth allometri negative. The relationship between high the shell of a to the weight of the y = 2.1467x-3.3947 is growth allometri negative. The regression equation is of the relation between the shell of a thick to the weight of the y = 2.0258x- 2.7291 is growth allometri negative. The form of a thin body as much as 54.11%, the form of the body of 39.24% proportional, the form of a plump body as much as 6.65%.